2014
DOI: 10.1590/s1982-21702014000200019
|View full text |Cite
|
Sign up to set email alerts
|

Estudo preliminar da preferência de cor para rota e seta de manobra em mapas de sistemas de guia de rota

Abstract: RESUMOOs Sistemas de Navegação e Guia de Rota em Automóvel (SINGRA), comerciais ou gratuitos, vêm adotando diferentes projetos gráficos para os mapas que apoiam a tarefa de navegação. O objetivo deste trabalho é avaliar a preferência de um grupo de motoristas pela cor da rota e da seta de manobra para mapas destes sistemas. Um total de 54 motoristas (27 homens e 27 mulheres) participou de um experimento que ocorreu em um automóvel estacionado. Duas representações cartográficas foram produzidas para avaliar a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
0
7
0
6
Order By: Relevance
“…Some of the participants who preferred the route in black commented that the route in blue can be confused with hydrographic features. In the research by Ramos et al (2014a), the authors verified drivers' preference about the color of the route (blue versus black) with a group of drivers with normal color vision. These authors reported that the route in black was preferable because it helped to increase contrast on the map and allowed association with road asphalt.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the participants who preferred the route in black commented that the route in blue can be confused with hydrographic features. In the research by Ramos et al (2014a), the authors verified drivers' preference about the color of the route (blue versus black) with a group of drivers with normal color vision. These authors reported that the route in black was preferable because it helped to increase contrast on the map and allowed association with road asphalt.…”
Section: Discussionmentioning
confidence: 99%
“…Since the process of communicating navigational information can have serious impact on traffic safety, researchers have pointed out the importance of evaluating usability issues by considering individual differences (Burnett 1998;Green et al 1993;Labiale 2001;Liu 2001;Pugliesi, Decanini and Tachibana 2009;Burnett et al 2013b;Lin and Chen 2013;Ramos et al 2014a). Some research works about RGNS map design take the cartographic communication process into account (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The graphic design of maps of two different scales (1:3,000 and 1:6,000) was based on perceptive grouping and figure-ground segregation as noted by MacEachren (1995), Dent, Torguson and Hodler (2009) and Slocum et al (2009). Additionally, the results of Ramos et al (2014b) relating to driver preference for the color of the route and direction arrow were adopted. The graphic design of the map elements is shown in Table 3.…”
Section: Graphic Design Of Mapsmentioning
confidence: 99%